Assessing nutritional diversity of cropping systems in African villages - Remans, R.; Flynn, D.F.B.; Clerck, F. de; Diru, W.; Fanzo, J.C. (Public Library of Science, 2011)
In Sub-Saharan Africa, 40% of children under five years in age are chronically undernourished. As new investments and attention galvanize action on African agriculture to reduce hunger, there is an urgent need for metrics that monitor agricultural progress beyond calories produced per capita and address nutritional diversity essential for human health. In this study we demonstrate how an ecological tool, functional diversity (FD), has potential to address this need and provide new insights on nutritional diversity of cropping systems in rural Africa.